Positron bunching and electrostatic transport system for the production and emission of dense positronium clouds into vacuum - Aghion, Stefano; Bräunig, Philippe; Demetrio, Andrea; Oberthaler, Markus K. (Nuclear instruments & methods in physics research. Section B, Beam interactions with materials and atoms, 2015)
We describe a system designed to re-bunch positron pulses delivered by an accumulator supplied by a positron source and a Surko-trap. Positron pulses from the accumulator are magnetically guided in a 0.085T field and are injected into a region free of magnetic fields through a μ-metal field terminator. Here positrons are temporally compressed, electrostatically guided and accelerated towards a porous silicon target for the production and emission of positronium into vacuum. Positrons are focused in a spot of less than 4mm FWTM in bunches of ∼8ns FWHM. Emission of positronium into the vacuum is shown by single shot positron annihilation lifetime spectroscopy.
Gesehen am 15.07.2021